APLIKASI TOTAL QUALITY MANAGEMENT (TQM) DALAM MANAJEMEN PENDIDIKAN ISLAM - hidayatul, Siti Nur (e-Journal STAI Muhammadiyah Tulungagung, 2013)
Full scale Quality Management (TQM) happening if school or Islamic Junior High School does development and education upgrade chronically. Full scale Quality Management (TQM) happening if school has done quality surety management (Full scale Quality Assurance). Its mean is quality surety management happens if headmaster perform its leadership function with every consideration, so becomes support for management success all education component. In other words that curriculum business success, studentâs business, things medium business, subjective business with society, finances and administration will very dependent on madrasah (school) headmaster or head leadership as top leader.